Odpowiedzi

Najlepsza Odpowiedź!
2009-12-03T16:22:14+01:00
A) (x-1)(x-1)+x²-1=2x²-2
x²-x-x+1+x²-1=2x²-2
x²-x-x+x²-2x²= -2-1+1
-2x= -2 |: (-2)
x= 1

b) (x-4)²=(x-2)(x+2)
x²-8x+16=x²-4
x²-8x-x²= -4-16
-8x= -20 |(-8)
x=2½

c)x²+(3x-3)(x+1)=1+(2x-1)²
x²+ 3x²+3x-3x-3=1+4x²-4x+1
x²+ 3x²+3x-3x-4x²+4x= 1+3
4x= 4
x=1

proszę;]
2009-12-03T16:23:09+01:00
Rozwiąż równanie.
a) (x-1)(x-1)+x²-1=2x²-2
x²-2x+1+x²-1=2x²-2
2x²-2x=2x²-2 |-2x²
-2x=-2
x=1

b) (x-4)²=(x-2)(x+2)
x²+16-8x=x²-4 |-x²
16-8x=-4 |-16
-8x=-20
x=2,5

c)x²+(3x-3)(x+1)=1+(2x-1)²
x²+(3x²+3x-3x-3)=1+4x²-4x+1
4x²-3=2+4x²-4x |-4x²
-3=2-4x |-2
-5=-4x
x=1 i 1/4